2012
DOI: 10.1097/dcr.0b013e31823e2d18
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Risk Profiling and Gene Signature Modeling to Predict Risk of Complications After IPAA

Abstract: In this IPAA patient cohort, mutations in the 10q21 locus and the PTGER4 gene were associated with Crohn's disease-like complications, whereas mutations in NOD2 and TNFSF15 correlated with severe pouchitis. Preoperative genetic analysis and use of such gene signatures hold promise for improved preoperative surgical patient selection to minimize these IPAA complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
2
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(11 citation statements)
references
References 42 publications
0
8
2
1
Order By: Relevance
“…This data differs from other countries where 34% was reported in Scotland [26] and 21.7% in Brazil [27], and differ widely from China (5.3%) [29] and Japan (10%) [30]. To date, there is still no clear explanation for this fact, but it may be influenced by ethnic background, geographic location [35], genetic information [36], diet [37] and some features of the UC, for example, the clinical course [38]. In our study, 20.6% of the patients had active acute pouchitis and 35.3% presented pouchitis in remission due to the adequate response to antibiotic treatment, in contrast with United States where 96% of the patients responded to antibiotic treatment [23].…”
Section: Discussioncontrasting
confidence: 48%
“…This data differs from other countries where 34% was reported in Scotland [26] and 21.7% in Brazil [27], and differ widely from China (5.3%) [29] and Japan (10%) [30]. To date, there is still no clear explanation for this fact, but it may be influenced by ethnic background, geographic location [35], genetic information [36], diet [37] and some features of the UC, for example, the clinical course [38]. In our study, 20.6% of the patients had active acute pouchitis and 35.3% presented pouchitis in remission due to the adequate response to antibiotic treatment, in contrast with United States where 96% of the patients responded to antibiotic treatment [23].…”
Section: Discussioncontrasting
confidence: 48%
“…The ileal pouch anal anastomosis (IPAA) is associated with high failure rates and poor functional outcomes[113], particularly for CD with NOD2 mutation which is associated with severe pouchitis[114,115]. Inflammation in the pouch is significantly higher for CD than for UC[116].…”
Section: Technical Considerations In Surgery For CDmentioning
confidence: 99%
“…This study was undertaken because previous studies have shown TNFSF15 to be associated with other colonic pathologies, namely IBD. 4 Its association with another inflammatory colonic disease, namely diverticulitis, thus seemed possible. 5,48,49 TL1A expression levels have been found to correlate with the severity of Crohn's inflammation and fibrostenosis in CD.…”
Section: Tnfsf15 and Tl1amentioning
confidence: 99%
“…[3][4][5][6] It plays a role in immunological defense through regulation of T-cell activation, maturation, and differentiation and thus may influence inflammation in diseases of the intestine. It is associated with inflammatory bowel disease (IBD), particularly with a severe phenotype in both ulcerative colitis (UC) and Crohn's disease (CD) as well as pouchitis after restorative proctocolectomy.…”
mentioning
confidence: 99%